2016
DOI: 10.3892/or.2016.5265
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of the combination of manumycin A and Immodin is associated with antiplatelet activity and increased granulocyte tumor infiltration in a 4T1 breast tumor model

Abstract: Manumycin A is a natural antibiotic isolated from Streptomyces parvulus with broad range of biological activities including antineoplastic activity in several in vitro and in vivo cancer models. Immodin [dialyzable leukocyte extract (DLE)] is a dialysate released from disintegrated blood leukocytes of healthy donors which exerts immunonormalizing effects on cell-mediated immune responses. The aim of the present study was to explore the antitumor potential of the combination of manumycin A and Immodin in an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…In our previous study, T. vulgaris L., applied in the same mouse model and doses as cinnamon, demonstrated significant reduction of 4T1 tumor volume in mice by more than 80% compared to the control group [7]. Mentioned significant therapeutic effects of plant substances are comparable with the antitumor efficacy of several synthetic drugs tested in the 4T1 mouse model of breast cancer [36][37][38]. The results of this and our previous preclinical rodent model studies confirmed our scientific assumption that the significant anticancer effect of whole plant functional foods is based more on a combination of several phytochemicals than on isolated molecules [2][3][4][5][6][7]39,40].…”
Section: Discussionmentioning
confidence: 80%
“…In our previous study, T. vulgaris L., applied in the same mouse model and doses as cinnamon, demonstrated significant reduction of 4T1 tumor volume in mice by more than 80% compared to the control group [7]. Mentioned significant therapeutic effects of plant substances are comparable with the antitumor efficacy of several synthetic drugs tested in the 4T1 mouse model of breast cancer [36][37][38]. The results of this and our previous preclinical rodent model studies confirmed our scientific assumption that the significant anticancer effect of whole plant functional foods is based more on a combination of several phytochemicals than on isolated molecules [2][3][4][5][6][7]39,40].…”
Section: Discussionmentioning
confidence: 80%
“…I-CRP shows selective cytotoxicity to solid cancer cells [16,20,21,23], such as MCF-7, BT-474, MDA-MB-453, A-427, Calu-1, U937, and L5178Y-R cell lines [20,21,23]. Other types of DLE have also shown antitumor activity in prostate cancer [29] and can be used in combination with chemotherapies [30] and with antibiotics as manumycin in mouse breast cancer (4T1) [31]. Since these cytotoxic analyses were done in solid cancer cell lines, its effect in cancer lymphocytes was unknown especially because there were doubts about its efficacy in leukemia, as it increases lymphocyte number in lung [14] and breast [15] cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Manumycin A was isolated from Streptomyces [28], and inhibits the prenylation of small G-protein [29]. The administration of manumycin A prevented the growth of triple-negative breast cancers, in which the expressions of estrogen, progesterone, and HER2 receptors were negative, in nude mice [29].…”
Section: Acidosis-dependent Anti-cancer Drugsmentioning
confidence: 99%
“…The administration of manumycin A prevented the growth of triple-negative breast cancers, in which the expressions of estrogen, progesterone, and HER2 receptors were negative, in nude mice [29]. Manumycin A was also shown to increase the efficacy of other anti-cancer drugs in animal models [28]. To the best of the author’s knowledge, no clinical trial using manumycin A has been reported.…”
Section: Acidosis-dependent Anti-cancer Drugsmentioning
confidence: 99%
See 1 more Smart Citation